Гематологічний профіль у сухостійних корів за різних сезонів року - Корейба, Людмила Володимирівна; Koreyba, Ludmila; Koreyba, L. V.; Koreyba, Lyudmila Volodymyrivna; Koreyba, L.; Koreiba, L. V.; Дуда, Юлія Вікторівна; Duda, Yuliya; Duda, Y. V.; Duda, J. V.; Duda, Julia; Duda, Y.; et al. (Kharkiv State Zooveterynary Academy, 2019)
Встановлено вірогідне зниження вмісту гемоглобіну у весняний період року (117,61±3,63г/л),у порівнянні з літнім (139,49±4,73 г/л, p < 0,01), осіннім (134,35±4,66 г/л, p < 0,01) та зимовим (132,40±4,95 г/л, p < 0,05). Водночас влітку на фоні найвищого вмісту гемоглобіну з низькою кількість еритроцитів спостерігалось вірогідне підвищення кольорового показника в 1,33 рази (p < 0,01), упорівнянні з весною. Влітку спостерігалось збільшення лейкоцитів до 10,33±0,46 г/л, але залишались у межах фізіологічної норми, а восени зниження до мінімуму – 8,33±0,31 г/л, а також вірогідна найбільша відсоткова кількість лімфоцитів (74,67±2,40 %) і базофілів (2,58±0,33 %) , у порівнянні з іншими періодами року. Вірогідне збільшення вмісту сегментоядерних нейтрофілів до 21,10±1,24 % спостерігали у весняні місяці та до 20,25±1,33 % – в осінні, на фоні зниження паличкоядерних нейтрофілів відповідно весною до 2,70±0,46% та восени до 4,30±1,02%, що свідчить про фізіологічний зсув формули нейтрофілів ліворуч в ці періоди року. Изучение обмена веществ в организме коров в зависимости от физиологического состояния, условий содержания и кормления при различных периодах года является необходимым условием направленного воздействия на их воспроизводительную способность и производительность. Сезон года существенно влияет на изменение числа эритроцитов, лейкоцитов, содержание гемоглобина, гематокритной величины и общее количество крови коров, независимо от их породы. Эти показатели являются самыми низкими в зимний период. Целью работы было изучение гематологического профиля у сухостойных коров в разные периоды года. Анализ гематологических показателей свидетельствует, что клеточный состав крови неодинаков в разные периоды года. При исследовании крови сухостойных коров выявлено достоверное снижение содержания гемоглобина в весенний период года (117,61 ± 3,63 г/л) по сравнению с летним (139,49 ± 4,73 г/л, Р < 0,01), осенним (134 , 35 ± 4,66 г/л, p < 0,01) и зимним (132,40 ± 4,95 г/л, Р < 0,05). В то же время летом на фоне высокого содержания гемоглобина с низким количеством эритроцитов наблюдалось достоверное повышение цветного показателя в 1,33 раза (Р < 0,01) по сравнению с весенним периодом. Летом прослеживалась тенденция увеличения лейкоцитов до 10,33 ± 0,46 г/л, но оставалась в пределах физиологической нормы, а осенью установлено их снижение до минимума – 8,33 ± 0,31 Г / л. Анализ лейкоцитарной формулы показал, что в летний период наблюдалась достоверное увеличение количества лимфоцитов (74,67 ± 2,40 %) и базофилов (2,58 ± 0,33 %) по сравнению с другими периодами года. Прослеживается достоверное увеличение содержания сегментоядерных нейтрофилов до 21,10±1,24 % в весенние месяцы и до 20,25±1,33 % – в осенние, на фоне снижения палочкоядерных нейтрофилов соответственно весной до 2,70 ± 0,46 % и осенью до 4,30 ± 1,02 %, что свидетельствует о физиологическом сдвиге формулы нейтрофилов влево в эти периоды года. Известно, что количество эозинофилов возрастает при стрессовых ситуациях. Так, сравнительный анализ количества эозинофилов в крови животных показал, что больше всего их значение в лейкоцитарной формуле было зимой, а при переходе с зимнего в весенний периоды установлено достоверное снижение эозинофилов в 1,62 раза (Р < 0,05). The study of metabolism in cows, depending on the physiological state, conditions of retention and feeding at different seasons of the year is a necessary condition for directed action on their reproductive capacity and productivity. The season of the year significantly affects on the change in the number of erythrocytes, leukocytes, hemoglobin content, hematocrit, and a total blood amount of cows, despite of their breed. These indices are the lowest in the winter. The goal of the work was to study the hematological profile of dry cows in different seasons of the year. Materials and methods. Studies were conducted on cows of the Bos taurus Holstein cows with milk productivity of 5–6 thousand kg for lactation during the physiological course of the dry period (day 11 to 53 of gestation) in different seasons of the year. Hematologic studies were performed according to the following indicators: (erythrocytes, hemoglobin, color index, SSE, leukocytes, monocytes, lymphocytes, rod and segmented neutrophils, basophils, and eosinophils), following conventional methods. Results of research and discussion. Analysis of hematologic indices shows that the cellular composition of blood is different at each season of the year. A significant decrease in hemoglobin content presented in the spring (117,61 ± 3,63g / l), compared with summer (139,49 ± 4,73g / l, p < 0,01), autumn (134,35 ± 4.66 g / l, p < 0,01), and winter (132.40 ± 4.95 g / l, p< 0,05) in the blood test of dry cows. At the same time, the highest hemoglobin content compared with the low erythrocyte counts increased by 1.33 times (p < 0,01), compared to spring. In summer the tendency of increased leukocytes to 10,33 ± 0,46 g / l was observed but remained within the limits of the physiological norm, and in autumn decreased to a minimum - 8,33 ± 0,31g / l. Analysis of the leukocyte formula showed that in summer the highest percentages of lymphocytes (74.67 ± 2.40%) and basophils (2.58 ± 0.33%) were observed compared to other periods of the year. The content of segmented nuclear neutrophils was increased to 21.10 ± 1.24 % in spring months, to 20.25 ± 1.33 % in autumn, because of decrease of rod - nucleated neutrophils, in spring to 2.70 ± 0.46% and in autumn to 4.30 ± 1.02%, indicating a physiological change of the neutrophil formula to the left during these periods of the year. It is known that the number of eosinophils increases in stressful situations. Thus, a comparative analysis of the number of eosinophils in the blood of animals showed that their largest value in the leukocyte formula was in winter, and during the transition from winter to spring period, a significant decrease of eosinophil was found in 1.62 times (p <0.05). Conclusions and prospects for further research. Seasonal variations of hematological status of calving cows of Holstein breed were revealed: in winter-spring period hemoglobin decreased to 117.61 ± 3.63 g / l and its growth in summer (139.49 ± 4.73 g / l); in summer months the decrease in the number of red blood cells to 6.88 ± 0.48 T / l, and a probable increase in the color index of 1.06 ± 0.07; increase in the total number of leukocytes in summer to 10.33 ± 0.46 g / l, but remained within the physiological norm, and decrease in autumn to a minimum - 8.33 ± 0.31 g / l; increasing the content of segmented neutrophils up to 21.10 ± 1.24 % and 20.25 ± 1.33 % in spring and in autumn months, respectively, and the content of basophils up to 2.58 ± 0.33 % in summer months only.
Гематологический профиль у сухостойных коров в разные периоды года
Hematological profile of dry cows in different seasons of the year
Корейба Людмила Володимирівна https://orcid.org/0000-0002-8658-1779 Дуда Юлія Вікторівна https://orcid.org/0000-0003-0892-0402
Keywords: гематологічне дослідження; hematological research; корови; cows; сухостійний період; dry period; морфологічні показники; morphological indices